Crazy paving, de quién es la culpa? - Maria João Tavares; Filipa Gonçalves (Sociedade Galega de Medicina Interna, 2020)
Crazy paving is a pulmonar high resolution computed tomography pattern of disease where areas of ground glass attenuation with superimposed septal thickening are observed. It is frequently observed in several types of pneumonia (caused by atypical agents, in patients with chronic microaspirations due to gastrointestinal pathologies), in pulmonary tumors, in sarcoidosis and at alveolar proteinosis. The next images shows a 61-year-old man with personal history of smoking habits and a prostatic tumor (Gleason 7) that appears to the emergency department due to dyspnea, fever and cough. At pulmonary auscultation there were no alterations. He performed some complementary diagnostic tests that showed elevated inflammatory parameters, respiratory insufficiency and a chest X-ray with bilaterally dispersed infiltrate. He performed a thoracic computed tomography that showed a bilateral infiltrated pattern - "crazy paving like". The patient was hospitalized with the diagnosis of suspected atypical pneumonia in an immunosuppressed patient. He was medicated with azithromycin 500mg/day/5days, with improvement of clinical status and resolution of the clinical situation. The IgM Mycoplasma pneumonia serology was positive. After 1 month he performed another thoracic computed tomography with resolution of the bilateral infiltrated.